STRATEGIC EFFORTS OF BINCANGSYARIAH.COM AND ISLAMI.CO EDITORIALS IN SPREADING COUNTER-NARRATIVE EXTREMISM ON THE INTERNET - Rahman, Muh. Fudhail; Irsyadi, Muhamad Masrur; Ferdiansyah, Hengki; Suma, Muhammad Amin; Trinanda, Desip (al-Balagh : Jurnal Dakwah dan Komunikasi, 2023)
The increasing religious enthusiasm of some Indonesians has become a target for extremist actors to spread their ideas and concepts. In fact, extremism can threaten the integrity of the nation and state. This article aims to discover the strategies Islami.co and Bincangsyariah.com used in conducting counter-narratives of extremism through online media. Islami.co and Bincangsyariah.com are moderate Islamic media involved in the Countering Violent Extremism (CVE) program through the United Nations Development Program (UNDP). This article uses a qualitative approach with content analysis techniques over supported data which are founders of Islami.co and Bincangsyariah.com as informants. Their published articles consist of counter-narrative extremism themes. The article primarily investigates the methods Islami.co and Bincangsyariah.com use to promote moderate Islamic content in the digital realm. The findings reveal that these sites engage in counter-narrative strategies by scrutinizing the arguments and claims of individuals or groups promoting extremism, thereby highlighting their fallacies. Moreover, they craft and disseminate alternative narratives that represent moderate Islam. As a result, Islami.co and Bincangsyariah.com have successfully exposed the flaws in the reasoning of pro-violence groups. However, further research is necessary to gauge the broader societal impact of these counter-narrative efforts.